Cellulose Nanofiber vs Nanocrystals From Pineapple Leaf Fiber: A Comparative Studies on Reinforcing Efficiency on Starch Nanocomposites. Issue 1 (16th August 2018) - Balakrishnan, Preetha; Gopi, Sreerag; Geethamma, V. G.; Kalarikkal, Nandakumar; Thomas, Sabu
Abstract : Cellulose nanofibers (CNFs) and nanocrystals (CNCs) are nanoscale materials obtained from nature by various physical and chemical treatments that has a strong reinforcing ability. CNFs and CNCs have different size, shape, viscosity, and other properties. This study focusses on comparative studies on reinforcing effect of CNFs and CNCs on thermoplastic starch (TPS). The nanocomposites with different weight percentage of reinforcing fillers are fabricated via solvent casting. The transparent TPS/CNF and TPS/CNC films are well characterized using dynamic mechanical analysis to study the effect of filler loading on viscoelastic behavior. All the nanocomposite films has better properties compared to neat TPS. But comparing the properties of CNFs and CNCs on the starch matrix, at some point of time, TPS/CNC composites are more transparent. But due to higher degree of entanglement, strong intermolecular attraction between starch and nanofibers, TPS/CNF composites are better, and the authors modeled the data with DMA and found that the nanofibers have better reinforcing ability and stress transfer character than CNCs. This type of comparative studies helps to find out the proper criteria to reinforce bio‐based material like starch for various applications.